PATU7 Autoimmune diseases after alemtuzumab treatment for multiple sclerosis: findings from a multicentre UK cohort. Issue 11 (22nd October 2010) - Cossburn, M D; Pace, A A; Jones, J; Ali, R; Ingram, G; Baker, K; Hirst, C; Zajicek, J; Scolding, N; Boggild, M; Pickersgill, T; Coles, A; et al.
Abstract : Alemtuzumab is a anti-CD52 humanised monoclonal antibody shown to be an effective treatment for relapsing multiple sclerosis (MS) in phase II studies but exhibits a unique adverse event profile. In limited follow-up studies development of autoimmune disease has been observed 20–30% of patients. Currently, the exact range and temporal evolution of autoimmune disease following treatment remains unclear but will have important implications for screening and safety monitoring. In this study we analyse prospective clinical and serological data from 225 patients treated with Alemtuzumab for a mean of 40.5 months (range 0.2–93.8). Novel autoimmune disease developed in 22.7%. Thyroid autoimmune disease was most common (17.8%) but a range of other autoimmune diseases including immune thrombocytopenic purpura, anti-GBM disease, neutropoenia, skin disorders and asymptomatic development of novel auto-antibodies was also observed. Risk of autoimmune disease was constant up to 55 months, following which there was a rapid decline, and independent of the number of treatments received or interval of dosage. Whilst established risk factors for autoimmune disease such as sex and age had no impact on autoimmune disease frequency, smoking was identified as a major risk factor with a relative risk of 4.95 for ever smokers. Risk of autoimmune disease in MS following alemtuzumab appears to be time limited and screening will need to continue for at least 5 years posttreatment. Individual risk for autoimmune disease is modified by external factors which should be incorporated within the counselling process prior to treatment.